Strategy for Using Sticker Tickets in Tourism Villages to Attract Tourists and Boost Income - Kurniawan, Andri; Margareta, Fitria; Mashudi, Sugeng; Agne, Aulia; Anggara, Bryan; Risma, Fany (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
Sendang Bulus is a unique water tourism destination that combines turtle conservation with various recreational activities such as fishing, ecotourism education, cultural tourism, and photography. This study aims to introduce and evaluate an innovative promotion strategy using entrance ticket stickers to attract more tourists and increase village revenue. The entrance ticket stickers feature appealing designs that highlight the unique aspects of Sendang Bulus, encouraging tourists to visit and engage with the various attractions available, including biodiversity exhibits, swimming pools, and various amusements like duck boats, mini trains, and ball baths. The methodology involved a detailed analysis of tourist behavior, the design and implementation of the ticket stickers, and subsequent monitoring of tourist numbers and revenue changes. Initial findings indicate a significant increase in tourist interest and income, with a 20% rise in ticket sales within the first three months of implementation. Furthermore, the innovative entrance ticket stickers have raised awareness about turtle conservation efforts. In conclusion, the "Entrance Ticket Sticker Innovation" has proven to be an effective strategy for promoting Sendang Bulus, enhancing tourist engagement, and increasing revenue. This strategy can serve as a model for other tourism villages aiming to boost their attractiveness and financial sustainability through creative marketing